Aortic Curvature Instead of Angulation Allows Improved Estimation of the True Aorto-iliac Trajectory. Issue 2 (February 2016) - Schuurmann, R.C.L.; Kuster, L.; Slump, C.H.; Vahl, A.; van den Heuvel, D.A.F.; Ouriel, K.; de Vries, J.-P.P.M.
Abstract : Objective: Supra- and infrarenal aortic neck angulation have been associated with complications after endovascular aortic aneurysm repair. However, a uniform angulation measurement method is lacking and the concept of angulation suggests a triangular oversimplification of the aortic anatomy. (Semi-)automated calculation of curvature along the center luminal line describes the actual trajectory of the aorta. This study proposes a methodology for calculating aortic (neck) curvature and suggests an additional method based on available tools in current workstations: curvature by digital calipers (CDC). Methods: Proprietary custom software was developed for automatic calculation of the severity and location of the largest supra- and infrarenal curvature over the center luminal line. Twenty-four patients with severe supra- or infrarenal angulations (≥45°) and 11 patients with small to moderate angulations (<45°) were included. Both CDC and angulation were measured by two independent observers on the pre- and postoperative computed tomographic angiography scans. The relationships between actual curvature and CDC and angulation were visualized and tested with Pearson's correlation coefficient. The CDC was also fully automatically calculated with proprietary custom software. The difference between manual and automatic determination of CDC was tested with a paired Student t test. A p -value was considered significant when two-tailed α < .05. Results: The correlation between actual curvature and manual CDC is strong (.586–.962) and even stronger for automatic CDC (.865–.961). The correlation between actual curvature and angulation is much lower (.410–.737). Flow direction angulation values overestimate CDC measurements by 60%, with larger variance. No significant difference was found in automatically calculated CDC values and manually measured CDC values. Conclusion: Curvature calculation of the aortic neck improves determination of the true aortic trajectory. Automatic calculation of the actual curvature is preferable, but measurement or calculation of the curvature by digital calipers is a valid alternative if actual curvature is not at hand.